Vibration analysis and noise mapping of automotive radiator system - Nur Farizah Diana, Abdul Razak (2020)
High speed of cooling fan operation is frequently used to manage the coolant temperature by ensuring adequate air flow through an automotive radiator, especially at low vehicle speeds or idle. However, an undesirable side effect of these fans is generation of flowinduced vibration and mechanical vibration, which is an annoyance to the society specifically to the passengers. Besides, internal flow of coolant inside the radiator’s tube also generates the vibrations into the system due to hydraulic imbalance. High flow configurations and high viscous properties of this coolant particularly affected the vibrations level. This thesis presents the experimental and theoretical analysis to investigate the changes in the characteristics of vibration measured and noise level on an automotive radiator resulting from variations of coolant flow rate, cooling fan speed and different type of coolant fluids. Also, this study aims to analyse the relationship between vibration and noise due to change in coolant flow rate, cooling fan speed and different types of coolant fluids hence the location of maximum sound pressure level (SPL) of automotive radiator can be identified. Water (100%) and Ethylene Glycol (EG)-water based (40:60) was used as working fluids operate with engine temperature range from 80 to 90 ℃. The radiator cooling fan speed were varied from 250 to 1250 RPM with coolant flow rates operating from 8.0 to 14.0 L/min. The measurement of vibrations used an accelerometer as a sensor while noise analysis is carried out by utilizing sound intensity mapping method where ½ inch a pair of microphones is used as a sensor. In vibration analysis, the vibration result increases 4-18 % when the coolant flow rate increases due to the dynamic motion of fluid flow inside the radiator’s tube increases. There is a larger increase (2-21 %) of vibration velocity when the fan speed increases which caused by high rotating fan speed that produced more frictions. Moreover, there is a slightly increased 4-10 % in vibrations level when the viscosity of coolant increases because of the repulsion force increases. In noise analysis, the noise level is generated in the frequency range from 25 to 10 kHz. The SPL result is strongly influenced by the rotational fan speed where the radiation noise from 750 to 1250 RPM makes the most significant contribution to overall noise of radiator system with around 32 dBA increases when increasing the fan speeds. The SPL value increases within 10 dBA when the coolant flow rate and coolant viscosity increase. The location of maximum SPL is identified and most located on the blade trailing edge area of the suction surface. In conclusion, noise increase when the vibration increased and high rotating of cooling fan speed is a dominant contributor to overall radiator noise, then it is followed by high coolant flow rates and high viscosity of coolant fluids.